2008
DOI: 10.1016/j.jneuroim.2007.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Male–female differences in the impact of β-adrenoceptor stimulation on resistance to experimental metastasis: Exploring the effects of age and gonadal hormone involvement

Abstract: We studied the development of sexual dimorphism in resistance to NK-sensitive experimental metastasis under baseline conditions and following adrenoceptor stimulation. With increasing age, baseline resistance to MADB106 lung tumor retention (LTR) increased in both sexes, but also the susceptibility to the tumor-enhancing effects of a β-adrenergic agonist, metaproterenol. Beginning at 13 weeks, males exhibited a 2-to 3-fold greater increase in LTR than females following adrenoceptor stimulation. This adult dimo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…These findings suggest that female F344 rats are more resilient than males to stress-induced NK suppression in general, and specifically to effects mediated through activation of the SNS. These sexual dimorphisms are consistent with our previous studies employing other stress paradigms [48], and specifically with respect to the impact of β-adrenergic receptor activation on NKCC [54, 55]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings suggest that female F344 rats are more resilient than males to stress-induced NK suppression in general, and specifically to effects mediated through activation of the SNS. These sexual dimorphisms are consistent with our previous studies employing other stress paradigms [48], and specifically with respect to the impact of β-adrenergic receptor activation on NKCC [54, 55]. …”
Section: Discussionsupporting
confidence: 92%
“…These effects are mediated through activation of leukocyte membrane receptors for these ligands, and intracellular initiation of the cAMP-PKA cascade common to both receptor systems [59, 60]. Potentially underlying the aforementioned sex differences in the impact of catecholamines on NKCC are the (i) menstrual cycle and female gonadal hormones that were shown to affect human and rat NK cell susceptibility to adrenergic stimulation [24, 61], presumably through modulating expression levels of adrenergic receptors on leukocytes [62], and (ii) testosterone that was shown to increase rat susceptibility to adrenergic suppression of in vivo levels of NKCC [55]. …”
Section: Discussionmentioning
confidence: 99%
“…Finally, we and others have reported that male rats are markedly more susceptible to the immunosuppressive and tumor-promoting effects of stress hormones, specifically catecholamines and corticosterone [26,56]. Human studies have reported similar dimorphism with respect to other physiological effects of these hormones.…”
Section: Discussionmentioning
confidence: 55%
“…Such comparisons may yield both practical and theoretical gains with potential clinical ramifications. Because sex differences in the stress responses [25,26], immunity [27] and tumor development [28] are well established, most studies have been conducted in both sexes and included a comparison of the findings in the different sexes.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancement of tumor progression is usually ascribed to b-AR-mediated decrease of NK activity (Shakhar and BenEliyahu 1998;Ben-Eliyahu et al 2000;Ben-Eliyahu et al 2000a), although noradrenaline has also been shown to inhibit the generation of specific antitumor cytotoxic T lymphocytes (Kalinichenko et al 1999). Interestingly, impairment of NK activity and reduced antitumor resistance following stress and b-AR stimulation seem to be affected by age as well as by gender (Page et al 2008). Recently, the prophylactic use of type-C CpG oligodeoxynucleotides (CpG-C ODN) was shown to improve NK activity and immunocompetence, potentially reducing metastatic dissemination after enhanced sympathetic stress responses (Goldfarb et al 2009) and in association with pharmacological blockade of b-ARs and COX inhibition it was proposed as a potential approach to limit postoperative immunosuppression and metastatic progression (Goldfarb et al 2011).…”
Section: Cancermentioning
confidence: 99%